LEARNING STRATEGIES IN FLUTE INTRODUCTION COURSES IN MUSIC EDUCATION STUDY PROGRAM, STATE UNIVERSITY OF JAKARTA - Sipahutar, Samuel (Jurnal Penelitian Musik, 2021)
This research takes the topic of learning strategies in the introductory course of flute which is a very important initial provision as a foundation or foundation in playing flute that must be owned by flute players. The purpose of this study was to obtain detailed data on how learning strategies in the introductory courses of flute at the Music Education Department of Universitas Negeri Jakarta, reviewed from flute learning strategies, especially basic techniques in playing flute. The object of research is the course Introduction to Flute. The research was conducted for 6 months during the covid-19 pandemic. The research method used is Descriptive Qualitative with Library Study approach. Data is collected through literature studies from various document sources such as journals, books, and articles. To supplement the data is also used the distribution of questionnaires to flute students who have already attended the introductory course of flute. The results showed that the Learning Strategy used by lecturers of Flute Prodi Pendidikan Musik is a combination of learning strategies that combine Direct, Interactive, and Empirical Learning strategies (Experiential). In addition, lecturers also emphasized the method of discussion and information sharing between students, so that students can think critically in every learning process. It can be concluded that the learning strategies used by lecturers introduction to flute can meet the needs of students to have basic skills of playing flute and is very equips to enter major flute courses.